2021
DOI: 10.21203/rs.3.rs-643446/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Perception And The Degree of Adoption By Urbanites Towards Urban Farming

Abstract: This research aims at finding out which are the factors that greatly impact city dwellers’ perception towards urban farming. The study also looks at the variables which strongly affect the residents’ ability to grasp the idea of adopting urban farming practices in the city of Kuala Lumpur, Malaysia. The four main factors included in this study are Confidence, Societal, Naturalness, and Pleasantness. A mixed-method approach was used involving both quantitative and qualitative, of a group of 129 respondents usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, the substantial initial investment required for hydroponics remains a major obstacle to widespread adoption in the region (Wood et al, 2020), as seen in Selangor, Malaysia, where that cost was identified as the primary deterrent to residents' willingness to engage in this practice (Hamdan et al, 2021). Meanwhile, in Singapore, the limited availability of technical training, installation support, and incentives has hindered broader adoption of hydroponics (Wong et al, 2010), while in Kuala Lumpur, the extent of participation in hydroponics was linked to people's confidence levels and satisfaction with the practice (Ahimaz et al, 2021). established rooftop gardens.…”
Section: Rooftop Gardeners In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the substantial initial investment required for hydroponics remains a major obstacle to widespread adoption in the region (Wood et al, 2020), as seen in Selangor, Malaysia, where that cost was identified as the primary deterrent to residents' willingness to engage in this practice (Hamdan et al, 2021). Meanwhile, in Singapore, the limited availability of technical training, installation support, and incentives has hindered broader adoption of hydroponics (Wong et al, 2010), while in Kuala Lumpur, the extent of participation in hydroponics was linked to people's confidence levels and satisfaction with the practice (Ahimaz et al, 2021). established rooftop gardens.…”
Section: Rooftop Gardeners In Asiamentioning
confidence: 99%
“… Notable exceptions include work by Ahimaz et al (2021), Hamdan et al (2021), and Hamzah et al (2016) in Malaysia and and Pham Thi Minh Khuyen (2019) and Pham and Turner (2020) in small Vietnamese cities.…”
mentioning
confidence: 99%